Screening the risk factors of type 2 diabetes mellitus in minor ethnic Bishnupriya Manipuri community in Bangladesh - Singha, Swapan K.; Emran, M. Shah; Sinha, Sharadindu K.; Sinha, Sunia; Ahmed, Kamal U.; Tahite, Dihan (International Journal of Research in Medical Sciences, 2024)
Background: Type 2 diabetes mellitus (T2DM) development involves various interrelated risk factors, including age, gender, obesity, and inactivity. However, research lacks insights into the risk factors within the minor ethnic Bishnupriya Manipuri community in Bangladesh. This study aimed to identify T2DM risk factors within this community. Methods: This survey-based prospective observational study was conducted in different villages of Kamalgonj Upazila under the Moulvibazar district in Bangladesh from March 2023 to June 2023 enrolled 280 individuals using purposive sampling. Data collection involved a questionnaire, verbal agreement, and diagnostic documentation. Analysis utilized Microsoft Office and the student’s t-test. Results: Participants exhibited a 1:1.2 male-female ratio, with 64% aged 36-65. 43% were housewives, 55% engaged in moderate work, 15% smoked, and 41% had a family history of diabetes. Diabetic cases accounted for 39%, with an average age of 57.39±11.99 years, significantly higher than non-diabetic cases (46.79±17.93 years). Diabetic cases also showed significantly higher waist circumference (94.11±6.63 cm versus 84.71±14.76 cm) and body mass index (BMI) (26.12±7.61 kg/m2 versus 21.44±6.97 kg/m2). Conclusions: T2DM predominantly affects older individuals in the Bishnupriya Manipuri community. Increased waist circumference, overweight, and obesity emerged as significant risk factors for T2DM within this population.